Carbon black, carbon black production method, composition for electrode, electrode, and secondary battery

JP2025032162AActive Publication Date: 2025-03-11DENKA CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024205960
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-02-05
Filing Date
2024-11-27
Publication Date
2025-03-11
Estimated Expiration
2042-01-21

AI Technical Summary

Benefits of technology

【0021】 本発明によれば、コバルト含有量が極めて少なく、二次電池用導電材として好適に利用可能なカーボンブラックが提供される。また本発明によれば、上記カーボンブラックの製造方法が提供される。更に本発明によれば、上記カーボンブラックを含有する電極用組成物、電極及び二次電池が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025032162000001_ABST
    Figure 2025032162000001_ABST
Patent Text Reader

Abstract

To provide carbon black that has an extremely small cobalt content and can be suitably used as a conductive material for secondary batteries.SOLUTION: Provided is carbon black in which an oil absorption amount is 150 mL / 100 g or more and 400 mL / 100 g or less, and a cobalt content is 20 ppb or less as measured by high frequency induced coupled plasma-mass spectrometry.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to carbon black and a method for producing the same, as well as an electrode composition, an electrode, and a secondary battery each containing the carbon black. [Background technology]

[0002] Carbon black has been used as a conductive material and the like, and the development of carbon black having various characteristic values ​​has been investigated (for example, Patent Document 1).

[0003] Moreover, Patent Document 2 describes a method for producing high-purity furnace black by a specific production method. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2009-035598 A [Patent Document 2] JP 2002-105355 A Summary of the Invention [Problem to be solved by the invention]

[0005] In recent years, the demand for secondary batteries has increased due to the increased demand for portable electronic devices, and there is a demand for materials constituting secondary batteries that can reduce the defective rate.

[0006] Carbon black is an example of a material used as a conductive material for secondary batteries. However, the carbon black produced by the method described in Patent Document 2, although having a high purity, does not have excellent properties as a conductive material for secondary batteries.

[0007] Therefore, an object of the present invention is to provide carbon black that has an extremely low cobalt content and can be suitably used as a conductive material for secondary batteries. Another object of the present invention is to provide a method for producing the carbon black. A further object of the present invention is to provide an electrode composition, an electrode, and a secondary battery that contain the carbon black. [Means for solving the problem]

[0008] One aspect of the present invention relates to carbon black having an oil absorption of 150 mL / 100 g or more and 400 mL / 100 g or less and a cobalt content of 20 ppb or less as measured by high-frequency inductively coupled plasma mass spectrometry.

[0009] In one embodiment, the cobalt content may be less than or equal to 15 ppb.

[0010] The carbon black according to one embodiment has a BET specific surface area of ​​35 m 2 / g or more 400m 2 / g or less.

[0011] The carbon black according to one embodiment has a BET specific surface area of ​​130 m 2 / g or more 400m 2 / g or less, the oil absorption may be 200 mL / 100 g or more and 400 mL / 100 g or less, and the BET specific surface area may be S(m 2 When the oil absorption is A (mL / 100g), the ratio S / A may be 0.3 to 2.5.

[0012] In one embodiment, the ratio S / A may be 0.4 to 2.5.

[0013] In one embodiment, the ratio S / A may be 0.5 to 1.5.

[0014] The carbon black according to one embodiment may be acetylene black.

[0015] Another aspect of the present invention relates to a method for producing carbon black, the method including: a synthesis step of treating a raw material gas containing hydrocarbons in a cylindrical cracking furnace to obtain carbon black; and a purification step of removing magnetic foreign matter from the carbon black with a magnet to obtain the carbon black of the present invention.

[0016] In one aspect, the purification step may be a step of removing the magnetic foreign matter from the carbon black obtained in the synthesis step by contacting the carbon black with the magnet or placing the carbon black in the vicinity of the magnet.

[0017] In one embodiment, the maximum surface magnetic flux density of the magnet may be 1000 mT or more.

[0018] Yet another aspect of the present invention relates to a composition for an electrode, comprising the carbon black according to the present invention and an active material capable of absorbing and releasing lithium ions.

[0019] Yet another aspect of the present invention relates to an electrode comprising the above-mentioned electrode composition.

[0020] Yet another aspect of the present invention relates to a secondary battery including the above-mentioned electrode. Effect of the Invention

[0021] According to the present invention, there is provided carbon black having an extremely low cobalt content and suitable for use as a conductive material for secondary batteries. According to the present invention, there is also provided a method for producing the carbon black. Furthermore, according to the present invention, there are provided an electrode composition, an electrode, and a secondary battery each containing the carbon black. [Brief description of the drawings]

[0022] [Figure 1] FIG. 1 is a schematic cross-sectional view showing one embodiment of a cylindrical cracking furnace. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] Preferred embodiments of the present invention will now be described in detail.

[0024] (Carbon Black) The carbon black of this embodiment has an oil absorption of 150 mL / 100 g or more and 400 mL / 100 g or less, and a cobalt content of 20 ppb or less.

[0025] Such carbon black contains very little cobalt-based foreign matter, and can significantly suppress the occurrence of defects caused by cobalt-based foreign matter. In addition, the carbon black has a sufficient oil absorption capacity, so that when used as an electrode conductive material for a lithium secondary battery, for example, the carbon black can easily retain an electrolyte and efficiently supply lithium ions to the active material. In addition, the carbon black has good dispersibility, and can be uniformly dispersed, for example, among active materials. Therefore, the carbon black can realize a secondary battery with few defects and excellent battery performance.

[0026] The cobalt content of the carbon black is preferably 15 ppb or less, more preferably 13 ppb or less, and even more preferably 10 ppb or less.

[0027] In the present embodiment, the cobalt content of the carbon black is a value measured by inductively coupled plasma mass spectrometry. Specifically, the measurement by inductively coupled plasma mass spectrometry is carried out as follows.

[0028] <Measurement by high-frequency inductively coupled plasma mass spectrometry> Approximately 1 g of carbon black sample was weighed out in a quartz beaker and heated in an electric furnace at 800℃ for 3 hours in an air atmosphere. Next, 10 mL of mixed acid (hydrochloric acid + nitric acid = 7:3) and 10 mL or more of ultrapure water were added to the residue and dissolved by heating on a hot plate at 200℃ for 1 hour. After cooling, the solution was diluted and adjusted to 25 mL with ultrapure water and measured with a high-frequency inductively coupled plasma mass spectrometer (Agilent 8800, manufactured by Agilent).

[0029] The carbon black of the present embodiment may be a carbon material having aggregates (primary agglomerates) in which primary particles having a diameter of several tens of nm are fused together in a beaded shape, and further having agglomerates (secondary agglomerates) in which the aggregates are physically entangled with each other.

[0030] The BET specific surface area of ​​carbon black is, for example, 35 m 2 / g or more, preferably 50m 2 / g or more, more preferably 100m 2 / g or more, more preferably 130m 2 / g or more, more preferably 150m 2 / g or more, more preferably 170m 2 / g or more. For example, when used as an electrode conductive material for a lithium ion secondary battery, this increases the number of contacts between the active material and the current collector, which tends to provide a better conductivity. The BET specific surface area of ​​carbon black is, for example, 400 m 2 / g or less, preferably 350m 2 / g or less. This suppresses interactions between primary particles and entanglement between aggregates, improving dispersibility and achieving, for example, more uniform dispersion among active materials. That is, the BET specific surface area of ​​carbon black is, for example, 35 to 400 m 2 / g, 35-350m 2 / g, 50-400m 2 / g, 50-350m 2 / g, 100-400m 2 / g, 100-350m 2 / g, 130-400m 2 / g, 130-350m 2 / g, 150-400m 2 / g, 150-350m 2 / g, 170-400m 2 / g or 170~350m 2 / g.

[0031] The BET specific surface area of ​​carbon black is measured by the single point nitrogen adsorption method, Method B, described in JIS K 6217-2.

[0032] The oil absorption of carbon black is 150 mL / 100 g or more, preferably 180 mL / 100 g or more, more preferably 220 mL / 100 g or more, and even more preferably 260 mL / 100 g or more. 2 / g or more. This makes it easier for the carbon black to retain the electrolyte, and makes it easier for lithium ions to be supplied to the active material, making it easier to obtain better battery performance, for example, when used as an electrode conductive material for a lithium ion secondary battery. In addition, the oil absorption of the carbon black is 400mL / 100g or less, preferably 370mL / 100g or less, and more preferably 350mL / 100g or less. This reduces the entanglement of the agglomerates, improving dispersibility, and achieving, for example, more uniform dispersion between the active materials. That is, the oil absorption of the carbon black may be, for example, 150 to 400 mL / 100g, 150 to 370 mL / 100g, 150 to 350 mL / 100g, 180 to 400 mL / 100g, 180 to 370 mL / 100g, 180 to 350 mL / 100g, 220 to 400 mL / 100g, 220 to 370 mL / 100g, 220 to 350 mL / 100g, 260 to 400 mL / 100g, 260 to 370 mL / 100g, or 260 to 350 mL / 100g.

[0033] The oil absorption of carbon black is a value measured by the method described in JIS K6221, Method B using DBP (dibutyl phthalate) as oil, and converted into a value equivalent to JIS K6217-4:2008 by the following formula (a). DBP absorption amount = (A-10.974) / 0.7833 …(a) [In the formula, A represents the value of DBP absorption measured by the method described in JIS K6221, Method B.]

[0034] The BET specific surface area of ​​carbon black is S(m 2When the amount of oil absorbed is A (mL / 100g), the ratio S / A may be, for example, 0.2 or more, preferably 0.3 or more, more preferably 0.4 or more, and even more preferably 0.5 or more. The ratio S / A is, for example, 3.0 or less, preferably 2.0 or less, more preferably 1.5 or less, and even more preferably 1.3 or less. This makes the balance of the number, size, and dispersibility of the aggregates more suitable for use as an electrode conductive material for a lithium-ion secondary battery, and makes it easier to supply lithium ions to the active material while forming sufficient contact points between the active material and the current collector, making it easier to obtain better battery performance. That is, the ratio S / A may be, for example, 0.2 to 3.0, 0.2 to 2.0, 0.2 to 1.5, 0.2 to 1.3, 0.3 to 3.0, 0.3 to 2.0, 0.3 to 1.5, 0.3 to 1.3, 0.4 to 3.0, 0.4 to 2.0, 0.4 to 1.5, 0.4 to 1.3, 0.5 to 3.0, 0.5 to 2.0, 0.5 to 1.5, or 0.5 to 1.3.

[0035] In a preferred embodiment, the carbon black has a BET specific surface area of ​​130 to 400 m 2 The carbon black may have a molecular weight of 1000 to 2000 mL / g, an oil absorption of 200 to 400 mL / 100 g, and a ratio S / A of 0.3 to 2.5 (preferably 0.4 to 2.5, more preferably 0.5 to 2.5, and even more preferably 0.5 to 1.5). Such carbon black has excellent electronic conductivity, ion conductivity, and dispersibility, and is therefore particularly suitable for use as a conductive material. Such carbon black is produced, for example, by a method of injecting oxygen gas, which will be described later.

[0036] In addition, within the ranges of the BET specific surface area and oil absorption amount of this embodiment, the larger the ratio S / A, the more difficult it tends to be to remove magnetic foreign matter. The carbon black of this embodiment is intentionally designed to have a ratio S / A within the above range while reducing the cobalt content, thereby achieving both the excellent effect as a conductive material described above and the reduction of problems caused by magnetic foreign matter.

[0037] The carbon black in this embodiment is preferably acetylene black.

[0038] The carbon black of the present embodiment can be produced by the following method.

[0039] (Method of manufacturing carbon black) The method for producing carbon black according to the present embodiment includes a synthesis step of treating a raw material gas containing hydrocarbons in a cylindrical cracking furnace to obtain carbon black, and a purification step of removing magnetic foreign matter from the carbon black obtained in the synthesis step with a magnet to obtain carbon black having an oil absorption of 150 mL / 100 g or more and 400 mL / 100 g or less and a cobalt content of 20 ppb or less.

[0040] In the synthesis step, the raw material gas is treated in a cylindrical cracking furnace. The cylindrical cracking furnace may, for example, include a pyrolysis section for carrying out a pyrolysis reaction of hydrocarbons and an aging section for reforming the pyrolysis reaction product.

[0041] The cylindrical cracking furnace may further include a supply port for supplying a raw material gas to the thermal decomposition section, and a recovery port for recovering the produced carbon black from the maturation section.

[0042] From the viewpoint of making the carbon black more homogenous and more efficiently removing magnetic foreign matter in the purification step described later, the cylindrical cracking furnace preferably has a ratio (D1 / D2) of the diameter D1 of the heat dividing section to the diameter D2 of the aging section of 1.2 to 2.2, and a ratio (L1 / L2) of the length L1 of the pyrolysis section to the length L2 of the aging section of 0.4 to 1.0. This allows the raw material gas supplied to the pyrolysis section to remain, and the completion of the pyrolysis reaction and the formation of carbon aerosol due to the development of aggregates can be more reliably carried out.

[0043] The ratio (D1 / D2) is preferably 1.3 to 1.8, and the ratio (L1 / L2) is preferably 0.6 to 0.8. That is, the ratio (D1 / D2) may be, for example, 1.2 to 2.2, 1.3 to 2.2, 1.2 to 1.8, or 1.3 to 1.8, and the ratio (L1 / L2) may be, for example, 0.4 to 1.0, 0.6 to 1.0, 0.4 to 0.8, or 0.6 to 0.8.

[0044] In the thermal decomposition section, the raw material gas supplied is preferably retained at a temperature of 1900°C or higher for 30 to 150 seconds. By setting the retention time to 30 seconds or more, the completion of the thermal decomposition reaction and the formation of carbon aerosol due to the development of a chain structure can be more reliably carried out. Furthermore, by setting the retention time to 150 seconds or less, the aggregation of the carbon aerosol is suppressed, and it becomes easier to obtain carbon black from which magnetic foreign matter can be more easily removed in the high purification step described below.

[0045] In the maturation section, the pyrolysis reaction product supplied from the pyrolysis section preferably resides at a temperature of 1700°C or higher for 20 to 90 seconds. By setting the residence time to 20 seconds or more, it becomes easier to obtain higher quality carbon black by modifying the carbon aerosol and strengthening the aggregates. In addition, by setting the residence time to 90 seconds or less, it becomes easier to obtain carbon black from which magnetic foreign matter can be more easily removed in the high purification step described below.

[0046] The residence velocities in the pyrolysis section and the aging section can be appropriately adjusted by adjusting the linear gas velocity of the gas flowing through each section. The residence time in the aging section is preferably shorter than the residence time in the pyrolysis section. That is, the linear gas velocity in the aging section is preferably faster than the linear gas velocity in the pyrolysis section.

[0047] Fig. 1 is a schematic cross-sectional view showing one embodiment of a cylindrical cracking furnace. The cylindrical cracking furnace 10 shown in Fig. 1 includes a thermal cracking section 1 and a maturation section 2. The cylindrical cracking furnace further includes a nozzle (supply port) 3 for supplying a raw material gas to the thermal cracking section 1.

[0048] In this embodiment, the raw material gas preferably contains acetylene as the first carbon source. The content of the carbon source (e.g., acetylene) in the raw material gas is, for example, 10% by volume or more, preferably 20% by volume or more, more preferably 30% by volume or more, and may be 100% by volume. The content of each component in the raw material gas is shown as a volume ratio based on the volume at 150°C and 1 atm.

[0049] The raw material gas may further contain one or more other carbon sources in addition to the first carbon source (e.g., acetylene). Examples of the other carbon sources include saturated hydrocarbons such as methane, ethane, and propane, unsaturated hydrocarbons such as ethylene, propylene, and butadiene, and aromatic hydrocarbons such as benzene, toluene, and xylene. By combining these carbon sources, the reaction temperature can be changed to increase or decrease the specific surface area of ​​the carbon black. The carbon source is preferably selected from the group consisting of unsaturated hydrocarbons such as acetylene, ethylene, and propylene, and aromatic hydrocarbons such as benzene and toluene. In addition, petroleum fractions such as gasoline, kerosene, light oil, and heavy oil may be used as the carbon source.

[0050] When the raw material gas contains acetylene and another carbon source, the ratio of the other carbon source to acetylene (volume of the other carbon source / volume of acetylene) may be, for example, 0.01 or more. The ratio of the other carbon source to acetylene (volume of the other carbon source / volume of acetylene) may be, for example, 99 or less, preferably 50 or less, more preferably 30, and may be 10 or less, or 2 or less. That is, the ratio (volume ratio) of the other hydrocarbon to acetylene may be, for example, 0.01 to 99, 0.01 to 50, 0.01 to 30, 0.01 to 10, or 0.01 to 2.

[0051] The raw material gas may further contain water vapor gas, oxygen gas, hydrogen gas, carbon dioxide gas, etc. As these gases, it is preferable to use high purity gases with a purity of 99.9% by volume or more. By using such high purity gases, it tends to be easier to produce carbon black with less magnetic foreign matter and stable BET specific surface area and oil absorption.

[0052] The content of the water vapor gas may be, for example, 0 to 80 parts by volume, preferably 0.1 to 70 parts by volume, more preferably 1 to 60 parts by volume, and even more preferably 3 to 55 parts by volume, relative to 100 parts by volume of the carbon source (e.g., acetylene) in the raw material gas. When the content of the water vapor gas is within the above range, the BET specific surface area of ​​the carbon black tends to be larger. That is, the content of the water vapor gas may be, for example, 0 to 80 parts by volume, 0 to 70 parts by volume, 0 to 60 parts by volume, 0 to 55 parts by volume, 0.1 to 80 parts by volume, 0.1 to 70 parts by volume, 0.1 to 60 parts by volume, 0.1 to 55 parts by volume, 1 to 80 parts by volume, 1 to 70 parts by volume, 1 to 60 parts by volume, 1 to 55 parts by volume, 3 to 80 parts by volume, 3 to 70 parts by volume, 3 to 60 parts by volume, or 3 to 55 parts by volume, relative to 100 parts by volume of the carbon source (e.g., acetylene) in the raw material gas.

[0053] In the synthesis process, it is preferable to supply oxygen gas to the pyrolysis section together with the raw material gas, and it is more preferable to supply the oxygen gas to the pyrolysis section by spraying the oxygen gas from around the supply port through which the raw material gas is supplied to the pyrolysis section.

[0054] The cylindrical cracking furnace preferably has an oxygen gas nozzle near the raw material gas supply port, and more preferably has a plurality of nozzles disposed at equal intervals so as to surround the supply port. The number of nozzles is preferably 3 or more, more preferably 3 to 8.

[0055] The cylindrical cracking furnace may also be equipped with a nozzle having a multiple tube structure (e.g., a double tube structure, a triple tube structure, etc.) having a raw material gas supply port and an injection port for injecting oxygen gas from the periphery thereof. In the case of a double tube structure, for example, the raw material gas may be injected from a gap on the inner tube side, and the oxygen gas may be injected from a gap on the outer tube side. In the case of a triple tube structure consisting of an inner tube, a middle tube, and an outer tube, for example, the oxygen gas may be injected from a gap formed by the outer wall of the middle tube and the inner wall of the outer tube, and the raw material gas may be injected from the remaining gap.

[0056] The amount of oxygen gas injected is not particularly limited unless the production yield of carbon black is taken into consideration. Carbon black can be produced even if more oxygen gas than necessary is injected. From the viewpoint of obtaining carbon black having the above-mentioned suitable oil absorption amount, the amount of oxygen gas injected may be, for example, 0 to 200 parts by volume relative to 100 parts by volume of the carbon source (e.g., acetylene) in the raw material gas, and is preferably 0.1 to 190 parts by volume, more preferably 0.5 to 180 parts by volume, and even more preferably 1 to 160 parts by volume. That is, the injection amount of oxygen gas may be, for example, 0 to 200 parts by volume, 0 to 190 parts by volume, 0 to 180 parts by volume, 0 to 160 parts by volume, 0.1 to 200 parts by volume, 0.1 to 190 parts by volume, 0.1 to 180 parts by volume, 0.1 to 160 parts by volume, 0.5 to 200 parts by volume, 0.5 to 190 parts by volume, 0.5 to 180 parts by volume, 0.5 to 160 parts by volume, 1 to 200 parts by volume, 1 to 190 parts by volume, 1 to 180 parts by volume, or 1 to 160 parts by volume, relative to 100 parts by volume of the carbon source (e.g., acetylene) in the raw material gas.

[0057] In the synthesis process, for example, the BET specific surface area and oil absorption amount of the resulting carbon black can be increased or decreased by adjusting the addition rate of hydrocarbons other than acetylene, the amount of oxygen gas injected, etc.

[0058] The cobalt content in the carbon black obtained in the synthesis process may be, for example, greater than 20 ppb, 30 ppb or more, 50 ppb or more, or 80 ppb or more.

[0059] The purification step is a step of removing magnetic foreign matter from the carbon black obtained in the synthesis step using a magnet.

[0060] The purification step may be, for example, a step of removing magnetic foreign matter from the carbon black obtained in the synthesis step by contacting the carbon black with a magnet or placing the carbon black in the vicinity of a magnet (e.g., passing the carbon black in the vicinity of a magnet).

[0061] There is no particular limitation on the magnet to be used, and for example, a magnet bar having a neodymium magnet packed inside a stainless steel 304 cylinder may be used.

[0062] The maximum surface magnetic flux density of the magnet is not particularly limited, but may be, for example, 700 mT or more, preferably 1000 mT or more, more preferably 1200 mT or more. This allows fine magnetic foreign matter attached to the carbon black to be more strongly adsorbed, making it easier to obtain carbon black with a lower cobalt content. The upper limit of the maximum surface magnetic flux density of the magnet is not particularly limited, and may be, for example, 1400 mT or less. That is, the maximum surface magnetic flux density of the magnet may be, for example, 700 to 1400 mT, 1000 to 1400 mT, or 1200 to 1400 mT.

[0063] The purification step may be a step of removing magnetic foreign matter from the carbon black so that the cobalt content is 20 ppb or less (preferably 15 ppb or less, more preferably 13 ppb or less, and even more preferably 10 ppb or less). There is no particular restriction on the lower limit of the cobalt content, but the cobalt content in the carbon black may be, for example, 1 ppb or more, and from the viewpoint of cost and productivity, it may be 5 ppb or more, or 8 ppb or more. That is, the cobalt content in the carbon black may be, for example, 5 to 20 ppb, 5 to 15 ppb, 5 to 13 ppb, 5 to 10 ppb, 8 to 20 ppb, 8 to 15 ppb, 8 to 13 ppb, or 8 to 10 ppb.

[0064] (Application) The carbon black of this embodiment has a significantly low content of cobalt-based foreign matter and is therefore suitable for use as a conductive material for secondary batteries, a semiconductive layer for power cables, etc. In addition, the carbon black of this embodiment has an oil absorption amount within the above range and is therefore particularly suitable for use as a conductive material for secondary batteries.

[0065] The carbon black of the present embodiment can be suitably used as, for example, an electrode composition containing carbon black and an active material capable of absorbing and releasing lithium ions. As the active material in the electrode composition, any known active material can be used without any particular limitation.

[0066] Examples of the active material include: Lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), layered lithium manganese oxide (LiMnO2), and LiMn x Ni y Co z Layered compounds such as O2 (x+y+z=1, 0≦y<1, 0≦z<1, 0≦x<1); Li 1+x Mn 2-x O4 (x is 0 to 0.33), Li 1+x Mn 2-x-y M y O4 (M represents at least one metal selected from the group consisting of Ni, Co, Cr, Cu, Fe, Al, and Mg, x represents 0 to 0.33, and y represents 0 to 1.0, with the proviso that 2-xy>0), LiMnO3, LiMn2O3, LiMnO2, LiMn 2-x M x manganese-based compounds such as Li2Mn3MO8 (M is at least one metal selected from the group consisting of Co, Ni, Fe, Cr, Zn, and Ta, and x is 0.01 to 0.1) and Li2Mn3MO8 (M is at least one metal selected from Co, Ni, Fe, Cr, and Zn); Copper-lithium oxide (Li2CuO2); Iron-lithium oxide (LiFe3O4); Olivine compounds such as LiFePO4, LiMnPO4, LiMnFePO4, and Li2MPO4F (M represents at least one metal selected from the group consisting of Co, Ni, Fe, Cr, and Zn); Vanadium oxides such as LiV3O8, V2O5, Cu2V2O7; Disulfide compounds; Silicate compounds such as Li2MSiO4 (M represents at least one metal selected from the group consisting of Co, Ni, Fe, Cr, Zn, and Ta); Examples include Li2MO3·LiMO2 (M represents at least one metal selected from the group consisting of Mn, Co, Ni, Fe, Cr, and Zn), Fe2(MoO4)3, Li2S, and S.

[0067] The secondary battery of the present embodiment includes an electrode containing the above-mentioned electrode composition. In the secondary battery of the present embodiment, the positive electrode and / or the negative electrode may contain the above-mentioned electrode composition, and it is preferable that the positive electrode contains the above-mentioned electrode composition.

[0068] In the secondary battery of this embodiment, the electrode that does not contain the electrode composition and the configuration other than the electrode are not particularly limited, and electrodes and configurations in known secondary batteries can be used without particular limitation.

[0069] Although the preferred embodiments of the present invention have been described above, the present invention is not limited to the above-described embodiments. EXAMPLES

[0070] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0071] Example 1 The mixture ratio of the raw material gas was 86% by volume of acetylene gas and 14% by volume of other carbon sources (toluene gas), and the gas was sprayed from a nozzle installed at the top of a cylindrical cracking furnace at a spray speed of 6.5 m / s. Carbon black was produced by utilizing the thermal decomposition and / or combustion reaction of the acetylene gas, and the carbon black was collected in an intermediate tank from a bag filter directly connected to the bottom of the furnace. (Synthesis process) The collected carbon black was passed through a transfer pipe equipped with a magnetic foreign matter collecting magnet (a magnet bar filled with a neodymium magnet in a stainless steel 304 cylinder with a diameter of 20 mm and a length of 300 mm, with a maximum surface magnetic flux density of 1000 mT) and collected in a product tank (high purification process), and carbon black (CB1) was obtained. Using the obtained CB1, a conductive composition for electrodes and an electrode for batteries were produced by the methods described below, and each evaluation was performed. The evaluation results are shown in Table 1.

[0072] Example 2 Carbon black (CB2) was obtained in the same manner as in Example 1, except that the mixture ratio of the raw material gas was changed to 100% by volume of acetylene gas. The obtained CB2 was used to prepare a conductive composition for electrodes and an electrode for batteries, and each evaluation was performed. The evaluation results are shown in Table 1.

[0073] Example 3 Carbon black (CB3) was obtained in the same manner as in Example 1, except that the mixture ratio of the raw material gas was changed to 71% by volume of acetylene gas, 15% by volume of oxygen gas, 12% by volume of water vapor, and 2% by volume of another carbon source (toluene gas). A conductive composition for electrodes and an electrode for batteries were produced using the obtained CB3, and each evaluation was performed. The evaluation results are shown in Table 1.

[0074] Example 4 Carbon black (CB4) was obtained in the same manner as in Example 1, except that the mixture ratio of the raw material gas was changed to 69 volume % acetylene gas, 8 volume % oxygen gas, 13 volume % water vapor, and 10 volume % other carbon source (toluene gas). The obtained CB4 was used to prepare a conductive composition for electrodes and an electrode for batteries, and each evaluation was performed. The evaluation results are shown in Table 1.

[0075] Example 5 Carbon black (CB5) was obtained in the same manner as in Example 1, except that the mixture ratio of the raw material gas was changed to 67% by volume of acetylene gas, 3% by volume of oxygen gas, 15% by volume of water vapor, and 15% by volume of another carbon source (benzene gas). A conductive composition for electrodes and an electrode for batteries were produced using the obtained CB5, and each evaluation was performed. The evaluation results are shown in Table 1.

[0076] Example 6 Carbon black (CB6) was obtained in the same manner as in Example 1, except that the mixture ratio of the raw material gas was changed to 51% by volume of acetylene gas, 27% by volume of oxygen gas, 20% by volume of water vapor, and 2% by volume of another carbon source (toluene gas). A conductive composition for electrodes and an electrode for batteries were produced using the obtained CB6, and each evaluation was performed. The evaluation results are shown in Table 1.

[0077] Comparative Example 1 Carbon black (CB7) was obtained in the same manner as in Example 1, except that the mixture ratio of the raw material gas was changed to 71% by volume of acetylene gas, 15% by volume of oxygen gas, 12% by volume of steam, and 2% by volume of other carbon sources (toluene gas), and the sample was taken from the intermediate tank and the high purification process was not performed. The obtained CB7 was used to prepare a conductive composition for electrodes and an electrode for batteries, and each evaluation was performed. The evaluation results are shown in Table 1.

[0078] Comparative Example 2 Carbon black (CB8) was obtained in the same manner as in Example 1, except that the mixture ratio of the raw material gas was changed to 67% by volume of acetylene gas, 3% by volume of oxygen gas, 15% by volume of steam, and 15% by volume of other carbon sources (benzene gas), and the sample was taken from the intermediate tank and the high purification process was not performed. The obtained CB8 was used to prepare a conductive composition for electrodes and an electrode for batteries, and each evaluation was performed. The evaluation results are shown in Table 1.

[0079] Comparative Example 3 As the carbon black of Comparative Example 3, SUPER P Li (manufactured by IMERYS Graphite & Carbon Co., Ltd., product name: SUPER P Li) was prepared.

[0080] Comparative Example 4 As the carbon black of Comparative Example 4, ECP (manufactured by Lion Specialty Chemicals, trade name: Carbon ECP) ​​was prepared.

[0081] <Evaluation method> (Measurement of cobalt content) Approximately 1 g of carbon black sample was weighed out in a quartz beaker and heated in an air atmosphere in an electric furnace at 800℃ for 3 hours. Next, 10 mL of mixed acid (hydrochloric acid + nitric acid = 7:3) and 10 mL or more of ultrapure water were added to the residue, and the mixture was heated and dissolved on a hot plate at 200℃ for 1 hour. After cooling, the solution was diluted and adjusted to 25 mL with ultrapure water, and the cobalt content was measured using a high-frequency inductively coupled plasma mass spectrometer (Agilent 8800, manufactured by Agilent).

[0082] (BET specific surface area measurement) The BET specific surface area of ​​carbon black was measured by the BET single-point method in accordance with JIS K 6217-2 B method using nitrogen as the adsorption gas under the condition of a relative pressure p / p0 = 0.30 ± 0.04.

[0083] (Oil absorption measurement) The oil absorption of carbon black is a value measured by the method described in JIS K6221, Method B using DBP (dibutyl phthalate) as oil, and converted into a value equivalent to JIS K6217-4:2008 by the following formula (a). DBP absorption amount = (A-10.974) / 0.7833 …(a) [In the formula, A represents the value of DBP absorption measured by the method described in JIS K6221, Method B.]

[0084] (Preparation of Dispersion of Electrode Composition) The solvent was N-methyl-2-pyrrolidone (manufactured by Kanto Chemical Co., Ltd., hereafter referred to as NMP), and the active material was LiNi 0.5 Mn 0.3 Co 0.2O2 (manufactured by Umicore, product name: TX10), polyvinylidene fluoride (manufactured by Arkema, product name: HSV900, hereinafter referred to as PVdF) as a binder, carbon black of the examples or comparative examples as a conductive material, and polyvinyl alcohol (manufactured by Denka, product name: B05, hereinafter referred to as polyvinyl alcohol) as a dispersant were prepared. 0.5 Mn 0.3 Co 0.2 O2 was weighed out and mixed to have a solid content of 98 mass%, PVdF was 2 mass%, carbon black was 1 mass%, and polyvinyl alcohol was 0.1 mass%. NMP was added to this mixture so that the solid content was 68 mass%, and the mixture was mixed until homogenous using a planetary centrifugal mixer (Thinky Corporation, Awatori Rentaro ARV-310), to obtain a dispersion of an electrode composition (positive electrode composition).

[0085] (Preparation of positive electrode) The prepared dispersion liquid of the electrode composition was applied to an aluminum foil (manufactured by UACJ) having a thickness of 15 μm by an applicator, and the film was pre-dried at 105° C. for one hour by placing the film in a dryer. Next, the film was pressed with a linear pressure of 200 kg / cm using a roll press machine to prepare a film having a thickness of 80 μm including the aluminum foil having a thickness of 15 μm. In order to remove volatile components, the film was vacuum-dried at 170° C. for 3 hours to obtain a positive electrode.

[0086] (Electrode evaluation) The prepared positive electrode was cut into a disk shape with a diameter of 14 mm, and the front and back were sandwiched between flat electrodes made of SUS304. With this in mind, the AC impedance was measured at an amplitude voltage of 10 mV and a frequency range of 0.1 Hz to 1 MHz using an electrochemical measurement system (Solatron, Function Generator 1260 and Potentiogalvanostat 1287). The intersection with the X-axis of the Cole-Cole plot was taken as the resistance value.

[0087] The evaluation results of the examples and comparative examples are shown in Table 1. In Table 1, the mixing ratio of "hydrocarbon gas" means the mixing ratio of other carbon sources.

[0088] [Table 1] [Explanation of symbols]

[0089] 1... thermal cracking section, 2... maturation section, 3... nozzle, 10... cylindrical cracking furnace.

Claims

1. The oil absorption amount is 150 mL / 100 g or more and 400 mL / 100 g or less, Carbon black having a cobalt content of 20 ppb or less as measured by inductively coupled plasma mass spectrometry.

2. 2. The carbon black of claim 1, wherein said cobalt content is 15 ppb or less.

3. BET specific surface area is 35m 2 / g or more 400m 2 The carbon black according to claim 1 or 2, wherein the molecular weight of the carbon black is 1 / g or less.

4. BET specific surface area is 130m 2 / g or more 400m 2 / g or less, The oil absorption is 200 mL / 100 g or more and 400 mL / 100 g or less, The BET specific surface area is S (m 2 4. The carbon black according to claim 1, wherein the ratio S / A is 0.3 to 2.5, where S / A is the amount of carbon absorbed by the carbon black and A is the oil absorption amount (mL / 100 g).

5. 5. The carbon black according to claim 4, wherein the ratio S / A is from 0.4 to 2.

5.

6. 6. The carbon black according to claim 5, wherein the ratio S / A is from 0.5 to 1.

5.

7. The carbon black according to any one of claims 1 to 6, which is acetylene black.

8. a synthesis step of treating a raw gas containing hydrocarbons in a cylindrical cracking furnace to obtain carbon black; a purification step of removing magnetic foreign matter from the carbon black using a magnet to obtain the carbon black according to any one of claims 1 to 7; A method for producing carbon black, comprising:

9. 9. The method according to claim 8, wherein the purification step is a step of contacting the carbon black obtained in the synthesis step with the magnet or arranging the carbon black in the vicinity of the magnet to remove the magnetic foreign matter from the carbon black.

10. The manufacturing method according to claim 8 or 9, wherein the magnet has a maximum surface magnetic flux density of 1000 mT or more.

11. 8. A composition for an electrode comprising the carbon black according to claim 1 and an active material capable of absorbing and releasing lithium ions.

12. An electrode comprising the electrode composition according to claim 11.

13. A secondary battery comprising the electrode according to claim 12.

Citation Information

Patent Citations

  • Carbon black for color and method for controlling undertone thereof

    JP1994136287A

  • High-purity carbon black

    JP2002105355A

  • Carbon black, method for purifying carbon black and semiconductive member containing carbon black

    JP2005220320A

  • Method for producing high-purity carbon black

    WO2010035871A1

  • Carbon black and production method therefor, and electricity storage device and conductive resin composition

    WO2015020130A1